Radiobiological analysis for evaluation of SIB hypofractioned treatment in H&N disease. (September 2016) - La Rosa, L.; Occhipinti, A.; Pedalino, A.; Rabito, A.
Abstract : Introduction: In this work we have analyzed a method to calculate a SIB hypofractionated treatment, starting from the prescription of a conventional treatment including a sequential boost (1.8–2 Gy/fr). Purpose: To calculate the SIB hypofractionated treatment we have started from the Biological Equivalent Dose (BED) calculation: we have estimated BED value for tumoral tissues (BED T ) and normal tissues (BED SANI ). Materials and methods: We have analyzed cases of patients with head and neck disease. We have started from the conventional treatment prescription and, according to the isoeffect theory, we (have) calculated the SIB hypofractionated treatment, evaluating BED T and BED SANI . To estimate, from a statistical point of view, the effects of the hypofractionated treatment compared to the conventional treatment including the sequential boost, two radiobiological quantities have been used: TCP (Tumor Control Probability) e NTCP (Normal Tissue Complication Probability). At last, we compared the prescribed conventional treatment and the hypofractionated treatment calculated, basing on the DVH obtained from the two techniques, for tumors and OAR, and on the TCP and NTCP calculation. Results: The accomplished assessments show, as expected, that in Hypofractionated treatment (SIB) we observe increasing TCP values, corresponding to a higher probability of tumor local control, as well as a decreased probability of damaging normal tissues (NTCP SIB  < NTCP conv ). Conclusion: This method to calculate the SIB hypofractionated treatment appears to be very successful in reducing the overall treatment time and in achieving a greater effect on the tumor and a reduced impact on normal tissues. Disclosure: None.